The impact of digital technology on sports consumption: evidence from Chinese college students - Yuan-Ji Zhong; Jiang-Wei Yang; Wen-Hao Guo; Yong-Shun Wang (Frontiers in Psychology)
BackgroundIn an increasingly digitalized world, the impact of digital technology on sports consumption behavior is a pivotal area of study, particularly among college students who are highly engaged with digital platforms.MethodsThis study investigates how digital technology use shapes college students’ sports consumption behavior, incorporating emotional experience as a mediator and symbolic perception as a moderator. Guided by the Stimulus-Organism-Response (S-O-R) framework and Symbolic Consumption Theory (SCT), data from 861 Chinese college students (511 males and 350 females) were analyzed using Structural Equation Modeling (SEM).ResultsResults reveal that digital technology use significantly enhances sports consumption, not only through a direct effect but also indirectly by improving emotional experience. Furthermore, symbolic perception amplifies the effect of emotional experience on consumption behavior. These findings highlight the dual psychological pathways through which technology influences sports-related decisions.ConclusionThe study offers theoretical contributions by integrating emotional and symbolic mechanisms, and provides practical insights for sports marketers and educators aiming to engage college students in digital-era consumption.